2019
DOI: 10.1111/jacf.12330
|View full text |Cite
|
Sign up to set email alerts
|

The Early Returns to International Hedge Fund Activism: 2000–2010

Abstract: In this summary of their recent article in the Review of Financial Studies, the authors provide an overview of the methods and findings of the first comprehensive study of worldwide hedge fund activism—one that examined the effectiveness of some 1,740 separate “engagements” of public companies by 330 different hedge funds operating in 23 countries in Asia, Europe, and North America during the period 2000‐2010. The study reports, first of all, that the incidence of shareholder activism is greatest in companies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“… 3 Despite Regulation Fair Disclosure, which restricts the information executives can share with select institutional investors, multiple studies have shown that investors can gain material knowledge during one-on-one meetings with management that allows them to make more informed trades (e.g., Becht, Franks, and Wagner, 2021). For example, Solomon and Soltes (2015: 329) explained that their analysis “suggests that private meetings confer benefits to a select group of investors who are able to gain access to management.” Hence, without such regulations governing what institutional investors can say, it becomes highly plausible that during such meetings portfolio managers and other institutional investor affiliates could pass information to executives to further promote the former’s interests. …”
mentioning
confidence: 99%
“… 3 Despite Regulation Fair Disclosure, which restricts the information executives can share with select institutional investors, multiple studies have shown that investors can gain material knowledge during one-on-one meetings with management that allows them to make more informed trades (e.g., Becht, Franks, and Wagner, 2021). For example, Solomon and Soltes (2015: 329) explained that their analysis “suggests that private meetings confer benefits to a select group of investors who are able to gain access to management.” Hence, without such regulations governing what institutional investors can say, it becomes highly plausible that during such meetings portfolio managers and other institutional investor affiliates could pass information to executives to further promote the former’s interests. …”
mentioning
confidence: 99%